2016
DOI: 10.1371/journal.pntd.0005091
|View full text |Cite
|
Sign up to set email alerts
|

Independent Origin and Global Distribution of Distinct Plasmodium vivax Duffy Binding Protein Gene Duplications

Abstract: BackgroundPlasmodium vivax causes the majority of malaria episodes outside Africa, but remains a relatively understudied pathogen. The pathology of P. vivax infection depends critically on the parasite’s ability to recognize and invade human erythrocytes. This invasion process involves an interaction between P. vivax Duffy Binding Protein (PvDBP) in merozoites and the Duffy antigen receptor for chemokines (DARC) on the erythrocyte surface. Whole-genome sequencing of clinical isolates recently established that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
89
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(104 citation statements)
references
References 39 publications
12
89
0
3
Order By: Relevance
“…vivax isolates collected in various malaria endemic settings had previously revealed that the PvDBP gene is frequently duplicated [17,18]. Here, we confirm again that amplification of PvDBPII is a common genomic event, which can frequently occur in isolates from areas where Duffy-negative phenotype is virtually absent such as Cambodia.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…vivax isolates collected in various malaria endemic settings had previously revealed that the PvDBP gene is frequently duplicated [17,18]. Here, we confirm again that amplification of PvDBPII is a common genomic event, which can frequently occur in isolates from areas where Duffy-negative phenotype is virtually absent such as Cambodia.…”
Section: Discussionsupporting
confidence: 84%
“…Initially, this epidemiological pattern suggested that the duplication of this gene was likely associated with the capability of the parasite to overcome the barrier of Duffy negativity. Since then, this hypothesis has been challenged by Hostetler et al [18] who found that PvDBP gene duplications were widespread even in malaria endemic areas in Southeast Asia where Duffy-negativity is not present. Another recent study [19] reported evidence of PvDBP gene amplification (3 and 8 copies) in two Duffynegative Ethiopian isolates.…”
Section: Author Summarymentioning
confidence: 99%
“…To the contrary, Hostetler et al . [65] recently demonstrated that P. vivax isolates with this Pv DBP duplication are globally widespread and are unlikely to be associated with the African DARC-negative phenotype. Rather, these authors proposed that upregulation of an alternative invasion pathway—perhaps mediated by the recently described Pv EBP ligand [66] or the greatly expanded Pv RBP family [67,68]— may facilitate invasion of DARC-negative erythrocytes.…”
Section: Plasmodium Vivax: a Long Neglected Pandemicmentioning
confidence: 99%
“…The PCR primers used to detect the Cambodian breakpoint observed to date may not amplify a product in samples that contain different breakpoints. As previous studies have suggested [13,14], copy number variations in the same gene can arise independently on different genetic backgrounds and result in distinct molecular breakpoints of amplification. Since qPCR methods do not rely on the location of primers in reference to an estimated breakpoint, they can be used broadly.…”
Section: Discussionmentioning
confidence: 90%